Virtual agent multimodal mimicry of humans. - Caridakis, George; Raouzaiou, Amaryllis; Bevacqua, Elisabetta; Mancini, Maurizio; Karpouzis, Kostas; Malatesta, Lori; Pelachaud, Catherine (Language Resources & Evaluation, 2007)
This work is about multimodal and expressive synthesis on virtual agents, based on the analysis of actions performed by human users. As input we consider the image sequence of the recorded human behavior. Computer vision and image processing techniques are incorporated in order to detect cues needed for expressivity features extraction. The multimodality of the approach lies in the fact that both facial and gestural aspects of the user’s behavior are analyzed and processed. The mimicry consists of perception, interpretation, planning and animation of the expressions shown by the human, resulting not in an exact duplicate rather than an expressive model of the user’s original behavior.